Recent process developments in beneficiation and metallurgy of rare earths: A review - Cheng, Shaokai; Li, Wenbo; Han, Yuexin; Sun, Yongsheng; Gao, Peng; Zhang, Xiaolong (Journal of rare earths, 2024)
Rare earth elements (REEs) are irreplaceable materials supporting low-carbon technology and equipment, and their commercial demand and strategic position are becoming increasingly prominent. With the continuous depletion of rare earth (RE) resources, developing high-efficiency beneficiation and eco-friendly metallurgical processes has attracted widespread attention. This paper reviews the major minerals exploited for RE production and their deposits, as well as the beneficiation and metallurgical processes of RE minerals. Bastnaesite, monazite, mixed RE ores, and ion-adsorption clays are the main raw materials in the world to date. RE-bearing ores (except ion-adsorption minerals) are generally beneficiated by flotation, gravity and magnetic separation techniques. The mainstream metallurgical processes for bastnaesite, monazite and mixed RE concentrates are oxidation roasting–HCl leaching, caustic soda decomposition and high-temperature concentrated sulfuric acid roasting, respectively. Ion-adsorption clays are directly processed by in situ leaching–precipitation/solvent extraction. To achieve the sustainable development of RE resources, it is essential to further explore innovative techniques to achieve comprehensive utilization and cleaner production. Rare earth resources are quite abundant worldwide and China has the largest reserves and production. Bastnaesite, monazite, and mixed RE ores are generally beneficiated by flotation, gravity and magnetic separation. Subsequently, metallurgical processes of oxidation roasting–HCl leaching, caustic soda decomposition and high-temperature concentrated sulfuric acid roasting are adopted. Ion-adsorption clays are directly processed by in situ leaching–precipitation/solvent extraction. [Display omitted] •Major RE minerals and their deposits are described.•RE beneficiation processes of flotation, gravity and magnetic separation are reviewed.•Industrial metallurgical techniques and lab-scale cleaner processes for RE concentrates are reviewed.•Development prospects of RE industry in beneficiation and metallurgy are summarized.